The role of psychological factors in questionnaire-based studies on routes of human toxoplasmosis transmission - Flegr, J; Hrdá, S; Tachezy, J (Central European journal of public health, 1998)
The paper studies impacts of particular toxoplasmosis risk factors (consumption of raw meat and contact with cats), their interactions, and their relationship with the personality of the subjects. Among 243 men and 343 women the frequency of subjects with antitoxoplasma immunity was 26.6% and 21.6%, respectively. The association of antitoxoplasma immunity (assessed by the toxoplasmin skin test) with the two risk factors was estimated by log-linear analysis. Reported contact with cats has no influence on the probability of having antitoxoplasma immunity (P = 0.23) while the consumption of raw meat increased this probability (P = 0.0008). Very strong positive association between the contact with cats and the raw meat consumption was found among subjects without toxoplasmosis (P = 0.0028), suggesting that among these persons some subjects either incorrectly assessed their exposition to the risk factors or provided false data during the interview. The results of logistic regression suggest that the contact with cat and the consumption of raw meat are associated with particular personality traits. However, these traits differ from those associated with antitoxoplasma immunity suggesting that the correlation between antitoxoplasma immunity and consumption of raw meat reflects epidemiological importance of the raw meat rather than a correlation of both factors (raw meat consumption and probability of acquiring toxoplasmosis) with the subjects personality.
Keywords: Surveys and Questionnaires; Sex Factors; stravovací zvyklosti; kočky; Humans; toxoplazmóza; lidé středního věku; prevalence; Female; rizikové faktory; Aged; dospělí; Toxoplasmosis; věkové faktory; senioři; lidé; zvířata; sexuální faktory; průzkumy a dotazníky; Adult; ženské pohlaví; Toxoplasma; Male; Middle Aged; Adolescent; Czech Republic; Prevalence; Cats; Age Factors; Animals; Česká republika; mužské pohlaví; Feeding Behavior; mladiství; Risk Factors